Extracting Polynomial Parameters

Algebra Level 5

Let f ( x ) = 2 x 3 + 5 x 2 7 x + 1 f(x) = 2 x^3 + 5 x^2 - 7 x + 1 and g ( x ) = f ( x 2 + 5 x + 1 ) g(x) = f(x^2 + 5x + 1) .

If { s i } \{ s_i \} are the roots of g ( x ) g(x) , find the value of the below expression.

i s i 2 \sum_i {s_i}^2


The answer is 64.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Aareyan Manzoor
Dec 24, 2015

f ( x ) = 2 ( x x 1 ) ( x x 2 ) ( x x 3 ) f(x)=2(x-x_1)(x-x_2)(x-x_3) then g ( x ) = 2 ( x 2 + 5 x + 1 x 1 ) ( x 2 + 5 x + 1 x 2 ) ( x 2 + 5 x + 1 x 3 ) g(x)=2(x^2+5x+1-x_1)(x^2+5x+1-x_2)(x^2+5x+1-x_3) we want the sum of the squares of roots of each factor, i.e 5 2 2 ( 1 x 1 ) + 5 2 2 ( 1 x 2 ) + 5 2 2 ( 1 x 3 ) 5^2-2(1-x_1)+5^2-2(1-x_2)+5^2-2(1-x_3) = 69 + 2 ( x 1 + x 2 + x 3 ) =69+2(x_1+x_2+x_3) by vietas formula, the sum is 5 2 \frac{-5}{2} . so = 69 + 2 ( 5 2 ) = 69 5 = 64 =69+2(\frac{-5}{2})=69-5=\boxed{64}

Akshat Sharda
Dec 23, 2015

My approach to calculate i s i 2 \displaystyle \sum_{i} s_{i}^2 was to use Newton's sums and for doing that we have to calculate first three coefficients of g ( x ) g(x) , i.e., coefficients of x 6 , x 5 x^6,x^5 and x 4 x^4 .

Coefficients of x 6 , x 5 x^6,x^5 and x 4 x^4 in 2 ( x 2 + 5 x + 1 ) 3 2(x^2+5x+1)^3 are 2 , 30 2,30 and 156 156 .

Coefficients of x 6 , x 5 x^6,x^5 and x 4 x^4 in ( x 2 + 5 x + 1 ) 2 (x^2+5x+1)^2 are 0 , 0 0,0 and 5 5 .

Therefore,

g ( x ) = 2 x 6 + 30 x 5 + 161 x 4 + p ( x ) g(x)=2x^6+30x^5+161x^4+p(x)

Where p ( x ) p(x) is the remaining part of g ( x ) g(x) .

Let P n = i s i n P_{n}=\displaystyle \sum_{i}s_{i}^n , so we need to find P 2 P_{2} .

By Newton's sums,

( 2 ) P 1 + 30 = 0 P 1 = 15 ( 2 ) P 2 + ( 30 ) P 1 + 322 = 0 P 2 = 64 (2)P_{1}+30=0\Rightarrow P_{1}=-15 \\ (2)P_{2}+(30)P_{1}+322=0\Rightarrow P_{2}=\boxed{64} .

did same...

Dev Sharma - 5 years, 5 months ago

there is an easier alternative, see my solution

Aareyan Manzoor - 5 years, 5 months ago
Hosam Hajjir
Dec 24, 2015

f ( x ) f(x) can be factored as follows:

f ( x ) = 2 ( x r 1 ) ( x r 2 ) ( x r 3 ) f(x) = 2 (x - r_1)(x - r_2)(x - r_3)

hence,

g ( x ) = 2 ( x 2 + 5 x + 1 r 1 ) ( x 2 + 5 x + 1 r 2 ) ( x 2 + 5 x + 1 r 3 ) g(x) = 2 (x^2 + 5 x + 1 - r_1)(x^2 + 5 x + 1 - r_2)(x^2 + 5 x + 1 - r_3)

Hence a solution s i s_i to g(x) = 0 , satisfies

s i 2 + 5 s i + 1 r j = 0 s_i^2 + 5 s_i + 1 - r_j = 0 .. .. .. .. .. Equation (1)

for i = 1 , 2 , . . . , 6 i = 1, 2, ...,6 where s 1 s_1 and s 2 s_2 are associated with r 1 r_1 , etc.

Now, since this is a quadratic equation in s i s_i , the sum of the two solutions is b -b , i.e.

s 1 + s 2 = s 3 + s 4 = s 5 + s 6 = 5 s_1 + s_2 = s_3 + s_4 = s_5 + s_6 = -5

Adding the entries of Equation (1) over i=1,2,...6, we obtain

i s i 2 + 5 i s i + i 1 i r j ( i ) = 0 \sum_i {s_i}^2 + 5 \sum_i {s_i} + \sum_i 1 - \sum_i r_{j(i)} = 0

where j ( 1 ) = j ( 2 ) = 1 , j ( 3 ) = j ( 4 ) = 2 , j ( 5 ) = j ( 6 ) = 3 j(1) = j(2) = 1, j(3) = j(4) = 2 , j(5) = j(6) = 3 .

Now

i s i = 3 ( 5 ) = 15 \sum_i {s_i} = 3 (-5) = - 15

i 1 = 6 \sum_i 1 = 6

i r j ( i ) = 2 ( r 1 + r 2 + r 3 ) = 2 ( 5 / 2 ) = 5 \sum_i r_{j(i)} = 2 (r_1 + r_2 + r_3) = 2 (-5/2) = -5

Therefore,

i s i 2 = 5 ( 15 ) 6 + ( 5 ) = 75 11 = 64 \sum_i s_i^2 = -5(-15) - 6 + (-5) = 75 - 11 = \boxed{64}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...